Intermittent Upwelling Events Trigger Delayed, Major, and Reproducible Pico‐Nanophytoplankton Responses in Coastal Oligotrophic Waters. Issue 5 (2nd March 2023) - Fuchs, R.; Rossi, V.; Caille, C.; Bensoussan, N.; Pinazo, C.; Grosso, O.; Thyssen, M.
Abstract: Pico‐nanophytoplankton organisms are dominant in oceanic oligotrophic areas but their adaptive growth rates make their contribution to the carbon cycle difficult to estimate. Here we address their response capacities after sporadic wind gusts causing upwelling events in a coastal Mediterranean station. When the water column is stratified, corresponding to oligotrophic conditions, these events generate intense short‐lived nutrient pulses and seawater temperature drops lasting 6 days on average with decreases up to 10°C. Using an automated flow cytometer and statistical rupture‐detection methods, we characterize the responses of five pico‐nanophytoplankton functional groups at a two‐hour frequency from September 2019 to November 2021. These events trigger delayed increases in both abundances and biomasses following similar patterns for most groups that can overpass spring bloom values, and are immediately followed by an overall decrease, suggesting a clear physical driver. These submesoscale events, due to their short duration, are poorly represented in coastal carbon budgets. Plain Language Summary: Short‐lived north‐westerlies in the Mediterranean Sea replace surface coastal waters with colder and potentially richer in nutrients deeper waters from offshore. This phenomenon, called a sporadic upwelling event, lasts only a few days after the wind stops and induces brutal environmental shifts. During summer, upwellings generate drops in surface water temperature of up to 10°C and are expected to impact significantly phytoplankton. Small phytoplankton are conspicuous for their fast response to environmental changes thanks to their high division rates (up to several times a day). As a result, the biological response to wind‐induced upwellings has to be studied using high‐frequency measurements. Using four attributes for each of the five studied phytoplankton groups, we show that the number of cells of most groups rose strongly in less than 2 days after the temperature drop according to remarkable repeatable patterns. Similarly, total biomass increased after less than 4 days. The reactions themselves lasted up to 5 days before returning near to the initial level. Brought back to a daily scale, the described phytoplankton reactions to local upwelling events can be as important as the ones observed during the spring bloom, regarded as the most important annual event. Key Points: Biomass peaks and daily rates of increase induced by the most extreme upwellings are of the same magnitude as the spring bloom ones Phytoplankton abundance/biomass reactions start less than 2 days/4 days after the upwelling onset and last 2–5 days During upwelling events, all biomasses (but Synechococcus ) median/maximum increases range 0–173/100%–400%, then sharply drop back to normal